The Influence of Corporate Governance, Tax Planning, and Perception of Tax Fairness on Corporate Tax Compliance in West Java Province (Sustainable Development Insights, 2026)
Tax compliance among corporate taxpayers is a critical factor in ensuring the sustainability of government revenue and supporting economic development. However, corporate tax compliance can be influenced by various internal and behavioral factors within organizations. This study aims to analyze the influence of corporate governance, tax planning, and perceptions of tax fairness on corporate tax compliance in West Java Province. The research employs a quantitative approach using primary data collected through questionnaires distributed to corporate taxpayers, involving 55 respondents consisting of finance managers, accountants, tax staff, and company owners. The measurement of research variables was conducted using a Likert scale, and the data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results of the analysis indicate that corporate governance, tax planning, and perceptions of tax fairness have positive and significant effects on corporate tax compliance. Corporate governance encourages transparency, accountability, and ethical financial practices that contribute to higher compliance with tax regulations. Tax planning practices also support corporate tax compliance by enabling companies to manage tax obligations efficiently while remaining within the boundaries of tax law. In addition, perceptions of tax fairness influence companies’ willingness to comply voluntarily with tax obligations when the tax system is perceived as transparent and equitable. Simultaneously, these three variables explain 54.9% of the variation in corporate tax compliance, indicating that they play an important role in shaping corporate taxation behavior. The findings of this study provide valuable insights for policymakers and tax authorities in designing policies that strengthen corporate governance, encourage responsible tax planning, and improve perceptions of fairness within the tax system to enhance corporate tax compliance.
Keywords: Corporate Governance; Tax Planning; Tax Fairness Perception; Corporate Tax Compliance; West Java Province